Highway designs: effects of heavy vehicles stability (2018)
From the perspective of heavy vehicles stability, some criteria of stability should be adhered to highway designs. In particular, the relationship between minimum radius, superelevation, slope angle, side friction, and design speed should be re-evaluated. In this regard, the static rollover threshold (SRT) is one of the most important factors used to define the stability of vehicles. This factor is highly dependent on the maximum lateral acceleration (ay) of a vehicle until it reaches the rollover threshold. This acceleration in turn is dependent on the vehicle speed and the radius of curvature. Taking into account the stability of vehicles, in this study the highways design is evaluated and compared with the classic design criterion. This study also suggests that in order to ensure driving safety, the State Highway Agencies should make a reevaluation of existing speed limits and the design of highway curves.